Every picture tells a story: framing and understanding the activism of convict criminology - Ross, Jeffrey Ian (2024)
Convict Criminology (CC) consists of three major initiatives. Although scholarship and mentoring have been dominant activities, understanding the activism/policymaking of CC is less well known. This paper reviews the primary United States based activities that CC has done in this area and suggests what it needs to do to assist the interests of individuals who are behind bars and those who are formerly incarcerated, as well as work towards the mission of the CC organization as a whole. Some of the areas where CC has participated politically include the news-making we have done (i.e. interviews with the news media) and the periodic statements released on social media by the American Society of Criminology’s Division of Convict Criminology. This paper will also consider the notion of praxis as applied to CC, in that some members consider their research, public speaking, and mentorship to be political actions worthy to be considered political activity.